2008
DOI: 10.1111/j.1744-9987.2008.00595.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Pediatric Fulminant Hepatitis Treated With Plasma Diafiltration

Abstract: Plasma diafiltration (PDF) is blood purification therapy in which simple plasma exchange is performed with a membrane plasma separator while dialysate flows outside the hollow fibers. A 14-year-old boy with fulminant hepatitis underwent two sessions of PDF and one session of hemodiafiltration. We infused filtered replacement fluid for artificial kidneys at a dialysate flow rate of 600 mL/h and a replacement flow rate of 450 mL/h. We infused fresh frozen plasma (1200 mL) and 25% albumin solution (50 mL) intrave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…We have previously reported on the effectiveness of PDF in patients with acute liver failure (7–9). Here, we report the results of a prospective multicenter trial using PDF in patients with liver failure.…”
mentioning
confidence: 98%
“…We have previously reported on the effectiveness of PDF in patients with acute liver failure (7–9). Here, we report the results of a prospective multicenter trial using PDF in patients with liver failure.…”
mentioning
confidence: 98%
“…The Evacure EC‐2 A plasma separator has a pore size of .01 mm, which is much smaller than that of the standard plasma separation membrane (0.2–0.4 mm). This membrane has a sieving coefficient of 0.3 for albumin and thus can selectively remove low or intermediate molecular weight albumin‐bound substances . In addition, coagulation factors are preserved in the process because this membrane has a sieving coefficient of 0 for fibrinogen .…”
Section: Discussionmentioning
confidence: 99%
“…Plasma diafiltration (PDF) is a blood purification therapy in which simple PE is performed using a selective membrane plasma separator (Evacure EC‐2 A plasma separator; Kuraray, Tokyo, Japan) while the dialysate flows outside the hollow fibers . PDF has some advantages compared with PE.…”
Section: Introductionmentioning
confidence: 99%
“…This membrane has a sieving coefficient of 0.3 for albumin and thus can selectively remove low‐ or intermediate‐molecular‐weight albumin‐bound substances. In addition, coagulation factors are preserved because this membrane has a sieving coefficient of 0 for fibrinogen and IgM . Li et al reported that PE with a membrane pore size of 0.03 μm adequately removed bilirubin and bile acid, a class of toxins bound to plasma protein in patients with severe viral hepatitis, and reduced the loss of essential plasma macromolecules .…”
Section: Discussionmentioning
confidence: 99%